Discrete geometry for computer imagery : 19th IAPR International Conference, DGCI 2016, Nantes, France, April 18-20, 2016. Proceedings /: 19th IAPR International Conference, DGCI 2016, Nantes, France, April 18-20, 2016. Proceedings. (2016) - Unknown
No abstract available